Behavioral Abnormalities and Circuit Defects in the Basal Ganglia of a Mouse Model of 16p11.2 Deletion Syndrome - Thomas Portmann; Mu Yang; Rong Mao; Georgia Panagiotakos; Jacob Ellegood; Gul Dolen; Patrick L. Bader; Brad A. Grueter; Carleton Goold; Elaine Fisher; Katherine Clifford; Pavitra Rengarajan; et al. (Cell Reports, 2014)
A deletion on human chromosome 16p11.2 is associated with autism spectrum disorders. We deleted the syntenic region on mouse chromosome 7F3. MRI and high-throughput single-cell transcriptomics revealed anatomical and cellular abnormalities, particularly in cortex and striatum of juvenile mutant mice (16p11+/−). We found elevated numbers of striatal medium spiny neurons (MSNs) expressing the dopamine D2 receptor (Drd2+) and fewer dopamine-sensitive (Drd1+) neurons in deep layers of cortex. Electrophysiological recordings of Drd2+ MSN revealed synaptic defects, suggesting abnormal basal ganglia circuitry function in 16p11+/− mice. This is further supported by behavioral experiments showing hyperactivity, circling, and deficits in movement control. Strikingly, 16p11+/− mice showed a complete lack of habituation reminiscent of what is observed in some autistic individuals. Our findings unveil a fundamental role of genes affected by the 16p11.2 deletion in establishing the basal ganglia circuitry and provide insights in the pathophysiology of autism.